1984
DOI: 10.1007/bf03189618
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue localization of doxycycline polyphosphate and doxycycline hydrochloride in the rat

Abstract: Two doxycycline derivatives Doxycycline polyphosphate and Doxycycline hydrochloride were administered to rats at a dose of 20 mg/kg body weight. Doxycycline tissue levels were determined using a microbiological assay. Only an insignificant fraction of the antibiotics was found to cross the blood brain barrier. Doxycycline was highly concentrated in excretory organs: liver, kidneys and caecum. The high intestinal drug level observed is probably related to the entero-hepatic cycle of this antibiotic. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
3
13
1
Order By: Relevance
“…Doxycycline is highly lipophilic and would be expected to be distributed widely in the chicken. Nevertheless, the V^m*) of 0.28 ± 0.02 I/kg determined in the present study was much lower than that reported for other species: 0.75 I/kg in adult humans (Raghuram & Krishnaswamy, 1982), 1.38 I/kg in calves (Riond et al, 1989), 1.5 to 3.5 I/kg in dogs (Michel et al, 1979), 2.28 I/kg in cows and ewes (Ziv & Sulman, 1974), 4.5 to 7 I/kg in rats (Michel et al, 1984) and 9.78 I/kg in goats (Jha et al, 1989). The lower value of apparent volume of distribution found in the present study may be attributed to higher plasma protein binding, as well as a lower gut reabsorption of drug in the chicken.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Doxycycline is highly lipophilic and would be expected to be distributed widely in the chicken. Nevertheless, the V^m*) of 0.28 ± 0.02 I/kg determined in the present study was much lower than that reported for other species: 0.75 I/kg in adult humans (Raghuram & Krishnaswamy, 1982), 1.38 I/kg in calves (Riond et al, 1989), 1.5 to 3.5 I/kg in dogs (Michel et al, 1979), 2.28 I/kg in cows and ewes (Ziv & Sulman, 1974), 4.5 to 7 I/kg in rats (Michel et al, 1984) and 9.78 I/kg in goats (Jha et al, 1989). The lower value of apparent volume of distribution found in the present study may be attributed to higher plasma protein binding, as well as a lower gut reabsorption of drug in the chicken.…”
Section: Discussioncontrasting
confidence: 71%
“…or oral administration in chickens could be described adequately by a two-compartment open model. Experiments performed in mammals (Ziv & Sulman, 1974;Michel et al, 1984;Jha et al, 1989;Riond et al, 1989) have led to the same conclusion. Disappearance of the drug from the plasma of chickens was characterized by an initial rapid distribution phase followed by a slower elimination phase.…”
Section: Discussionmentioning
confidence: 73%
“…No human PLTP mRNA was detected in brain tissue, probably because doxycycline poorly crosses the blood brain barrier (Michel et al 1984). The distribution pattern of murine PLTP in human PLTP expressing PLTPtg//rtTAtg mice is comparable with the pattern found in C57BL/6 wildtype mice (Jiang and Bruce 1995).…”
Section: Discussionmentioning
confidence: 58%
“…Tre-PLTPtg//rtTAtg Àdox 1.5 ± 1.0 0.0 ± 0.0* 1.5 ± 0.9* 0.9 ± 0.1** 0.9 ± 0.1 0.8 ± 0.1 0.5 ± 0.1 1.0 ± 0.1 * p < 0.001, versus Tre-PLTPtg//rtTAtg + dox * p < 0.001, versus Tre-PLTPtg + dox explained by doxycycline distribution between tissues: after oral doxycycline administration to rats, highest levels were measured in excretory organs (i.e., liver and kidney) (Michel et al 1984). No human PLTP mRNA was detected in brain tissue, probably because doxycycline poorly crosses the blood brain barrier (Michel et al 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation